Distribution of DJ-1, Parkinson's Disease-Related Protein PARK7, and Its Alteration in 6-Hydroxydopamine-Treated Hemiparkinsonian Rat Brain - Takashi Yanagida; Kazuyuki Takata; Masatoshi Inden; Yoshihisa Kitamura; Takashi Taniguchi; Kanji Yoshimoto; Takahiro Taira; Hiroyoshi Ariga (Elsevier, 2006)
DJ-1 has multiple functions and its dysfunction may be linked to the onset of familial Parkinson's disease PARK7. However, the function and distribution of DJ-1 is unclear. In this study, we determined DJ-1 distribution and change after intranigral injection of 6-hydroxydopamine (6-OHDA). Although distribution of DJ-1 immunoreactivity was not changed in cerebral cortex and striatum, 6-OHDA caused increase of DJ-1 in the particulate fraction and decrease in the cytosolic fraction in substantia nigra. At that time, DJ-1 shifted to acid forms. These results suggest that distributional changes, translocation, and acidic shift of DJ-1 may be compensatory responses to protect against 6-OHDA-induced oxidative stress. Keywords:: DJ-1, 6-hydroxydopamine, Parkinson's disease